Kansei: the creative mind in the visual analyzing process - Shaari, Nazlina (Korean Society of Design Science, 2016)
Background: Emotions are complex conscious states that play an essential role in our daily lives. They have a great influence on human perception, particularly concerning our thinking, learning and decisions. In design, product emotion plays an important role in encouraging product quality and sustainability. Several methods and tools exist and are used to in the process of evaluating users-emotional experiences with products. Emotion is important to design because virtually all the decisions we make are based on how we feel or how we anticipate we will feel. Kansei engineering is a consumer-oriented technique for new product development. In product design, for instance, clothing and fabric design can be applied to translate consumers’ favorite feelings or images into physical design elements. Methods: This paper aims to develop the process of evaluating users’ emotional experiences in a more accurate semantic dimension through Kansei. Image feature extraction is a key issue for concept recognition in images and particularly emotions. In analyzing the product images, KJ methods based on the affective model was used to develop the full range of emotional keywords. This method shows the potentiality, limitation and building of a new framework for understanding the semantic structure used by designers in the visual analysis process for fabric analysis of clothing. Another affective model from SD methods also needed to support all the data. Result: The results show that various methods of the affective model will be a good reference for design studies that are involved with users’ subjective emotional experience with product design. The emotional expression showed that it can be well engaged in the process of satisfied and dissatisfied or desired or undesired in product choices. Conclusions: The process of identifying consumer needs is an integral part of the larger product development process and most closely related to the conceptual design, design selection, competitive benchmarking and establishment of product specification. Kansei methods will lead to better perceptions and understanding of product images and forms.